Comparing the effects of the second OPEC oil price shock on income and resource allocation in four oil-poor developing economies: Ivory Coast, Kenya, South Korea, Turkey - Hermann Dick; Sanjeev Gupta; David P. Vincent; Herbert Voigt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1981)
The large OPEC-engineered real world oil price increases of the early and late 1970's have set in train, via a highly integrated international trade and finance system, significant resource transfers from energy-poor to energy-rich countries. In accommodating these resource transfers both energy exporting and importing economies have been confronted with adjustment pressures. In the case of the former group, these adjustment pressures have arisen from the need for these economies to accommodate a favourable shift in their foreign terms of trade, ostensibly by way of a redirection of resources from the international to the domestic account, thus permitting higher real national income. For energy-poor countries however the required adjustment process has much less palatable consequences for economic growth and the real income aspirations of the populations. Our concern in this paper is with a subset of the latter group - the so-called oil-poor developing countries. We focus in considerable detail on four such economies; Kenya, South Korea, Ivory Coast and Turkey. As well as representing various levels of oil 'poorness' these countries exhibit interesting differences in resource endowments, the industrial composition of their gross domestic products, the oil intensity of their industrial production technologies, the skill composition of their labour forces, their openness to world trade and their commodity composition of exports and imports. By means of multisectoral economy-wide models for each of these countries, we quantify the nature and extent of the adjustment pressures imposed on them by what has now become known as the second OPEC oil shock of 1978-80.
Keywords: 330